Guarantee of Human Right protection of Victimof Human Trafficking - yasa yasaakmal (JLAST : Journal of Law and Social Transformation, 2025)
Human trafficking is a phenomenon of human buying and selling transactions which is a crime in various countries, especially Indonesia, where Indonesia itself is the 4th most populous country in the world, this does not rule out the possibility of difficulty in finding employment so that residents can be lured by the lure of work and salaries that will be given when in fact they could become subjects or victims of human trafficking . In this journal we will discuss what and how the guarantee of human rights protection for victims of human trafficking is attempted by the government regarding victims of this criminal act of human trafficking in the law. In addition, this journal also reviews the role of the government, non-governmental organizations, and the community in guaranteeing the rights of victims, such as access to health services, legal guidance, and social reintegration. The research method in this journal uses normative juridical by taking a legislative and case approach and using qualitative descriptive data analysis.